Coexistence of multiple anti-neuronal antibodies in autoimmune encephalitis in China: A multi-center study - Qiao, Shan; Zhang, Shan-Chao; Wang, Zhi-Hao; Wang, Lei; Zhang, Ran-Ran; Li, Hai-Yun; Jin, Yang; Liu, Ling-Ling; Wang, Mei-Ling; Wang, Ai-Hua; Liu, Xue-Wu (Frontiers in Immunology, 2022)
Background: Given that the combination of multiple antibodies in autoimmune encephalitis (AE) is rare and its clinical significance is unclear, this study aimed to investigate the clinical characteristics and significance of overlapping multiple anti-neuronal antibodies in patients with AE. Methods: We conducted a retrospective analysis of the clinical characteristics, treatment, and prognostic details of 22 patients with multiple coexisting antibodies from multiple clinical centers in China. Results: Among the 276 patients who were AE antibody-positive, 22 (7.97%) had two or more antibodies. Among the 22 patients with coexisting AE-related antibodies, 14 patients (63.63%) were combined of cell surface and intracellular antibody, and the remaining 8 patients (36.36%) were detected to be cell surface antibody positive only. The main symptoms of the 22 patients in this cohort included fever, seizures, memory impairment, cognitive decline, and sleep disorders. Five (22.73%) patients had tumors, among whom four had small-cell lung cancers, and one had mediastinal tumors. A total of 20 patients were treated with steroids and intravenous immunoglobulin, and 18 showed varying degrees of symptomatic improvement after first-line immunotherapy. Three patients died of tumor progression or chemotherapy complications. Conclusion: The coexistence of multiple anti-neuronal antibodies in patients with AE may cause a superimposition and diversification of clinical manifestations. Combined paraneoplastic antibody positivity may be suggestive of an underlying malignancy.